2022
DOI: 10.3389/fgene.2022.784089
|View full text |Cite
|
Sign up to set email alerts
|

CircATRNL1 and circZNF608 Inhibit Ovarian Cancer by Sequestering miR-152-5p and Encoding Protein

Abstract: Background: CircRNAs have been found to be involved in the pathogenesis of various diseases. We aimed to explore the roles of circRNAs in ovarian cancer.Methods: The expression levels of circRNAs in ovarian cancer and normal ovarian tissues were analyzed using RNA sequencing. Fluorescent in situ hybridization (FISH), proliferation assays and transwell assays were used to assess the effects of circRNAs on ovarian cancer.Results: CircATRNL1 and circZNF608 were downregulated in 20 ovarian cancer tissues compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Circ_0025033 has been denmonstrated to promote ovarian cancer development via regulating miR3703p/SLC1A5 axis [30]. Differentially expression of hsa_circ_0007615 was first indirectly reported by Lyu et al using RNA sequencing in ovarian cancer [31], implicating the role of hsa_circ_0007615 as a critical regulator in EOC. Our results demonstrate that hsa_circ_0007615 is frequently up-regulated in EOC compared to normal ovarian tissues or cells.…”
Section: Discussionmentioning
confidence: 98%
“…Circ_0025033 has been denmonstrated to promote ovarian cancer development via regulating miR3703p/SLC1A5 axis [30]. Differentially expression of hsa_circ_0007615 was first indirectly reported by Lyu et al using RNA sequencing in ovarian cancer [31], implicating the role of hsa_circ_0007615 as a critical regulator in EOC. Our results demonstrate that hsa_circ_0007615 is frequently up-regulated in EOC compared to normal ovarian tissues or cells.…”
Section: Discussionmentioning
confidence: 98%
“…Circ_0000554 was reported to increase cell invasion and proliferation via sponging miR-567 in ovarian cancer ( Wang et al, 2022b ). Both circATRNL1 and circZNF608 were found to suppress ovarian cancer progression via sequestering miR-152-5p and regulating encoding protein ( Lyu et al, 2022 ). CircCERS6 was revealed to inhibit tumor development via modulation of miR-630 and RASSF8 in epithelial ovarian cancer ( Li et al, 2022a ).…”
Section: Circrnas In Ovarian Cancer Progressionmentioning
confidence: 99%
“…In a mouse intraperitoneal xenograft model, overexpression of circATRNL1 significantly reduced the number and weight of tumor nodules in the abdomen, suggesting that circATRNL1 effectively represses tumor growth and metastasis in vivo. Additionally, Lyu et al [ 179 ] suggested that circATRNL1 may act as a tumor suppressor by encoding a 131 amino acid protein in EOC cells. CircATRNL1 was downregulated in tumor samples from stage III-IV HGSC patients, as compared with paired normal ovarian tissues, and it inhibited proliferation, migration, and invasion of EOC cells.…”
Section: Circrnas As Potential Therapeutic Targetsmentioning
confidence: 99%